2014
DOI: 10.1080/09500340.2014.914596
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of charge transport in organic polymer donor/acceptor photovoltaic materials

Abstract: π-conjugated organic semiconductors have long been used as either holes or electrons transport materials. Recently, ambipolar charge carrier transport in these materials have been reported in many investigations. In this paper, we report on the basis of experimental results that the organic semiconductor (donor/acceptor) materials can be as good electrons transporters as these materials are holes transporters. In our study, the solution-processed unipolar diodes based on organic materials P3HT, VOPCPhO, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In our previous studies, [15,19] we found that the VOPcPhO show the ambipolar charge transport. In order to discuss the detailed charge transport behavior of the VOPcPhO, first we describe the current-voltage (J-V ) characteristics for the P3HT:VOPcPhO solar cells.…”
Section: -2mentioning
confidence: 76%
See 1 more Smart Citation
“…In our previous studies, [15,19] we found that the VOPcPhO show the ambipolar charge transport. In order to discuss the detailed charge transport behavior of the VOPcPhO, first we describe the current-voltage (J-V ) characteristics for the P3HT:VOPcPhO solar cells.…”
Section: -2mentioning
confidence: 76%
“…[14] The organic dyes from phthalocyanine group exhibits strong absorption in the visible solar spectral regime. [15] For instance, vanadyl 2, 9, 16, 23-tetraphenoxy-29H, 31H-phthalocyanine (VOPcPhO) shows the main absorption band in a range of 600 nm-800 nm, where the P3HT captivates very little. Due to the interesting properties of VOPcPhO, the BHJ of P3HT and PCBM are doped by VOPcPhO, in this study, in order to prepare a ternary blend system for BHJ solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the absorption coefficient of various layers in solar cells as a function of k(λ) are shown in figure 3. The light impinging on the solar cell induces charge carrier generation in the photoactive layer of the cell structure by the absorption of photons [47][48][49]. The charge carrier generation is directly related to this internal power flux by the following relation [45]:…”
Section: Numerical Modelling Approachmentioning
confidence: 99%